2022
DOI: 10.1039/d2ee00318j
|View full text |Cite
|
Sign up to set email alerts
|

Atomically dispersed single Ni site catalysts for high-efficiency CO2 electroreduction at industrial-level current densities

Abstract: Atomically dispersed and nitrogen-coordinated single Ni sites (i.e., NiNx moieties) embedded in partially graphitized carbon have emerged as effective catalysts for CO2 electroreduction to CO. However, much mystery remains behind...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(114 citation statements)
references
References 60 publications
3
111
0
Order By: Relevance
“…Reducing CO 2 toward the generation of valuable chemicals is one of the important strategies to achieve the dual carbon goal. 177 , 178 Wang et al. presented a carbon-confined indium oxide electrocatalyst for efficient CO 2 RR toward the direct production of formic acid.…”
Section: Applications Of Mof Nanocrystal-derived Hollow Porous Materialsmentioning
confidence: 99%
“…Reducing CO 2 toward the generation of valuable chemicals is one of the important strategies to achieve the dual carbon goal. 177 , 178 Wang et al. presented a carbon-confined indium oxide electrocatalyst for efficient CO 2 RR toward the direct production of formic acid.…”
Section: Applications Of Mof Nanocrystal-derived Hollow Porous Materialsmentioning
confidence: 99%
“…Single-atom catalysts (SACs) have drawn increasing attention in the field of catalysis thanks to the maximum utilization efficiency of atomically dispersed metals and their unsaturated coordination. [71][72][73][74][75] To prepare SACs, support is necessary to anchor and stabilize monodispersed metal sites. [76][77][78] Functional carbon has been widely demonstrated to be a type of suitable support for hosting single-atom metals due to its enhanced stabilization effects (Figure 4A).…”
Section: Single Metal Sitesmentioning
confidence: 99%
“…The GDE-based flow cells and MEA fuel cells are promising prototype reactors to achieve high-rate CO 2 reduction with industry-level currents, especially when combined with an anion exchange membrane. [75,185,186] However, most carbonbased catalysts were measured in H-type cells; future activity needs to be evaluated in flow cells and/or acual electrolyzers to evaluate their industry-level performance. In addition, how configurations of GDE, electrolyte, membrane, and size of reactor impact CO 2 RR performance remains not well understood, which should be further evaluated to establish optimal working conditions with enhanced energy conversion efficiency.…”
Section: Development Of Advanced Electrolyzersmentioning
confidence: 99%
“…Ni. [17][18][19][20][21][22][23][24][25] Recent studies have reported that an unsaturated coordinated NiNC catalyst with a broken D 4h symmetry is more optimized for the CO 2 RR than Ni-N 4 with the D 4h square-planar geometry. [26][27][28][29][30] The optimized electronic structure of Ni single atoms is significantly converted from that of bulk Ni, exhibiting high H* chemisorption energy and low energy barrier for CO 2 activation.…”
Section: (2 Of 9)mentioning
confidence: 99%
“…[ 4,15,16 ] Generally, a NiNC catalyst has a structure in which a support N atoms surrounds the center of a single Ni atom, exhibiting outstanding catalytic activity, unlike bulk Ni. [ 17–25 ] Recent studies have reported that an unsaturated coordinated NiNC catalyst with a broken D 4h symmetry is more optimized for the CO 2 RR than Ni‐N 4 with the D 4h square‐planar geometry. [ 26–30 ] The optimized electronic structure of Ni single atoms is significantly converted from that of bulk Ni, exhibiting high H* chemisorption energy and low energy barrier for CO 2 activation.…”
Section: Introductionmentioning
confidence: 99%